Level Playing Field or Politics as Usual? Equalization–Normalization in Direct Democratic Online Campaigns - Fischer, Michaela (2023)
Are digital technologies leveling the playing field or reinforcing existing power relations and structures? This question lies at the core of the equalization vs. normalization debate. The equalization thesis states that the affordances of digital technologies help less-powerful political actors to compete with their more resource-rich counterparts, thereby overcoming structural disadvantages inherent to the political landscape. The normalization thesis, in contrast, suggests that more powerful and resource-rich political actors outperform their weaker competitors in the digital sphere by establishing a more sophisticated online presence, thus reproducing existing power imbalances. An overwhelming majority of studies on the equalizing vs. normalizing effect of digital technologies focus on electoral campaigns or non-electoral periods. Direct democratic campaigns have not been adequately considered in previous studies. This study exploits the regularly held and institutionalized character of direct democratic votes in Switzerland. Specifically, it investigates political actors’ level of activity and generated engagement on Facebook and in newspapers during all direct democratic campaigns from 2010–2020. Applying the equalization vs. normalization lens to Swiss direct democratic campaigns over an 11-year timespan provides new insights into the status-quo preserving or altering effects of digital technologies. We find a tendency toward equalization in terms of Facebook activity and user engagement, and in a comparative perspective: Facebook campaigns are, on average, more balanced than newspaper advertisement campaigns, particularly since 2014.